The impacts to health coorellated with the consumption of coconut oil (Research, Society and Development, 2020)
Coconut oil is obtained from the pulp of fresh ripe coconut and can be extracted in different ways; either by artisanal, solvent or mechanical extraction. Unlike other vegetable oils, this one has a high content of medium chain fatty acids, which represent around 60% of its composition. This high content of medium chain fatty acids results in several benefits for the human organism. The present study aimed to evaluate the impacts caused by the daily consumption of coconut oil on the reduction of the abdominal circumference of men and women and on weight loss, its antibacterial activity against Staphylococcus aureus and, finally, its influence on the prevention and development of Alzheimer's. Most of the fatty acids present in coconut oil are rapidly absorbed in the intestine, generating energy quickly, even without suffering the action of pancreatic lipase enzymes. From the bibliographic review carried out, the effectiveness of coconut oil in reducing the abdominal circumference of men and women and weight loss was considered, in addition to its antibacterial activity against Staphylococcus aureus and its influence of coconut oil on prevention and development Alzheimer's disease. However, it was considered viable to consume up to 12 grams of coconut oil daily, and can be used as a substitute for other oils of vegetable origin.